1997
DOI: 10.1111/j.1600-0897.1997.tb00282.x
|View full text |Cite
|
Sign up to set email alerts
|

T‐Helper 2 Type Cytokine and Soluble Interleukin‐2 Receptor Levels in Seminal Plasma of Infertile Men

Abstract: These findings show: a) a lack of IL-4 in seminal plasma; b) similar SIL-2R levels in fertile and infertile seminal plasma; c) increased IL-6 secretion in seminal plasma of infertile subjects; and d) specific correlations of IL-6 with the main semen parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Several factors have been documented to exist in human semen, and the abnormality in their expression can cause infertility in men. For example, increased concentrations of interleukin-1 (IL-1), IL-2, IL-6, and tumor necrosis factor-a (TNF-a) in seminal plasma were found to be associated with poor semen quality (2)(3)(4)(5)(6)(7). Furthermore, some of the cytokines may affect physiologic events underlying male reproductive function.…”
mentioning
confidence: 97%
“…Several factors have been documented to exist in human semen, and the abnormality in their expression can cause infertility in men. For example, increased concentrations of interleukin-1 (IL-1), IL-2, IL-6, and tumor necrosis factor-a (TNF-a) in seminal plasma were found to be associated with poor semen quality (2)(3)(4)(5)(6)(7). Furthermore, some of the cytokines may affect physiologic events underlying male reproductive function.…”
mentioning
confidence: 97%
“…The authors found an increase of IL-1β in the group of patients with infertility but no other significant correlations between the parameters measured (Dousset et al, 1997). When Paradisi et al (1997) measured IL-4, IL-6 and the soluble interleukin-2 receptor in fertile and infertile men, they saw significant higher level of IL-6 in the infertile group compared with the fertile men. Furthermore IL-6 concentration correlated positively with leukocyte count and negatively with sperm count, motility and morphology.…”
Section: Effects Of Leukocytes On Sperm Functionmentioning
confidence: 99%
“…Semen samples were collected by masturbation and were treated as previously reported (18). An aliquot was used for routine sperm count (sperm concentration, motility, morphology, and viability, according to the World Health Organization guidelines [19]), spermioculture, and the evaluation of antisperm antibodies (immunobead binding test).…”
mentioning
confidence: 99%